2009
DOI: 10.1016/j.joen.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonsurgical Retreatment and Endodontic Surgery: A Systematic Review

Abstract: Introduction: The purpose of this systematic review was to compare the clinical and radiographic outcomes of nonsurgical retreatment with those of endodontic surgery to determine which modality offers more favorable outcomes. Methods: The study began with targeted electronic searches of MEDLINE, PubMed, and Cochrane databases, followed with exhaustive hand searching and citation mining for all articles reporting clinical and/or radiographic outcomes for at least a mean follow-up of 2 years for these procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
210
1
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(279 citation statements)
references
References 85 publications
14
210
1
26
Order By: Relevance
“…A meta-analysis 20 of rootend filling materials also reported that MTA was associated with the highest success when it was compared with IRM, Super-EBA or amalgam. The fact that the success rate of this study was similar to the weighted average success rate of periapical surgery 21 was a good evidence for the use of MTA as a root-end filling during the intentional replantation procedure.…”
Section: Discussionsupporting
confidence: 72%
“…A meta-analysis 20 of rootend filling materials also reported that MTA was associated with the highest success when it was compared with IRM, Super-EBA or amalgam. The fact that the success rate of this study was similar to the weighted average success rate of periapical surgery 21 was a good evidence for the use of MTA as a root-end filling during the intentional replantation procedure.…”
Section: Discussionsupporting
confidence: 72%
“…The rationale to explain the better time-related results is that only one file was used in the WS group, whereas four files were needed to perform the retreatment in the PTRS group. The PTRS consisted of three files; however, as suggested in previous studies, 3,8 further root canal refining is necessary because of the apical diameter of the D3 ProTaper Retreatment file (size 20). The last instrument designed to reach the working length does not permit complete cleansing action at the apical portion.…”
Section: Discussionmentioning
confidence: 99%
“…2 Problems related to canal anatomy, 3 as well as microbial factors, can explain failure rates of about 8% for treated canals. 4 In these cases, endodontic retreatment of the root canal system is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent or secondary intraradicular infection is a major cause of endodontic failure, and nonsurgical retreatment is indicated in these cases (1)(2)(3). Effective removal of filling material from the root canal system is essential to ensure a successful outcome of the retreatment procedure (4).…”
Section: Introductionmentioning
confidence: 99%